Case Report: Carcinoid heart disease with severe tricuspid regurgitation and concomitant patent foramen ovale causing severe hypoxia - Cronin, Michael; McAdam, Brendan (Frontiers in Cardiovascular Medicine, 2024)
This case report demonstrates a unique case in transcatheter management of complex concomitant structural cardiac issues in a frail patient. The primary regurgitant lesion in this case caused significant right to left shunting with severely debilitating hypoxaemia for the patient, requiring high volumes of ambulatory oxygen to compensate. We would to highlight like the role of multi-modality cardiac imaging demonstrated in this case, as well as the limited surgical data and poor outcomes in advanced disease with higher peri-operative complications, and finally that percutaneous correction of structural lesions may provide palliative relief with uncertain risk of recurrence.